Development of the Design Thinking Paradigm in the Context of the Transition to a New Technological Order - Valery Vladimirovich Glushchenko (Universitas Pendidikan Indonesia (UPI), 2023)
The subject of the article is the paradigm of design thinking as a method of scientific research and a method of project activity; the object of the work is design thinking in innovation activity; the purpose of the article is to increase the effectiveness of the practical use of design thinking in innovation activity; to achieve this goal, the following tasks are solved: studying the history of development and the essence of the design thinking method; research of design thinking as one of the ways of scientific research; description of design thinking as a method of innovative project activity; the research methods in this article are: historical and logical analysis, the theory of large systems, comparative analysis, heuristic methods; the method of design thinking; the scientific novelty of the article is associated with the formation of the paradigm of design thinking as one of the directions of modern theory of cognition and methodology of innovative project activity, including in the field of education.